Copyright Law Protection Against Unauthorized Use of Artwork In Commercial Products - Ananto, Riana Wulandari; Utama, Mohammad Wira; Ginting, Elianta; Amalia, Erna; Ekaningsih, Lailasari (Journal of Law, Politic and Humanities, 2025)
Copyright is an essential instrument within the Intellectual Property Rights (IPR) system, providing legal protection for works of art, literature, and science, including the economic and moral rights of the creator. In Indonesia, copyright regulation has evolved from Law No. 6 of 1982 to Law No. 28 of 2014, which affirms that copyright arises automatically based on the declarative principle and grants creators exclusive rights to exploit, use, and derive economic benefits from their works. This study employs a normative legal method by examining primary, secondary, and tertiary legal materials, including relevant legislation and court decisions. Copyright protection plays a crucial role in ensuring that creators receive recognition, control, and economic benefits from their works. The use of artistic works for commercial products without permission, such as the silhouette sketch of the “Tugu Selamat Datang” by PT Martina Berto Tbk, constitutes a violation of the creator’s economic and moral rights. Law No. 28 of 2014 emphasizes that copyright arises automatically once a work is realized, so any adaptation or use of a work still requires permission from the rights holder. The analysis indicates that copyright protection is vital for preventing unilateral exploitation of artistic works, ensuring legal certainty for creators, and promoting compliance within the creative industry